Short-term efficacy of intravitreal conbercept in treatment-naive patients with polypoidal choroidal vasculopathy - Peng Y; Zhang X; Li M; Liu B; Mi L; Zuo C; Wen F (Dove Medical Press, 2018)
Yuting Peng, Xiongze Zhang, Miaoling Li, Bing Liu, Lan Mi, Chengguo Zuo, Feng Wen State Key Laboratory of Ophthalmology, Zhongshan Ophthalmic Center, Sun Yat-sen University, Guangzhou, China Introduction: To evaluate the functional and morphological outcomes of intravitreal conbercept monotherapy in patients with polypoidal choroidal vasculopathy (PCV). Materials and methods: In this retrospective, observational case series study, we reviewed medical records of 48 eyes (48 patients) with naive PCV that were treated with a series of 3 monthly intravitreal injections of 0.5 mg of conbercept followed by as-needed injections (3+pro re nata). All patients completed at least 6 months of monthly follow-up. Changes in the best-corrected visual acuity, optical coherence tomography, and indocyanine green angiography were retrospectively evaluated. Results: At 6 months, the mean best-corrected visual acuity significantly improved from 0.89±0.35 (20/160 in Snellen equivalent) at baseline to 0.58±0.26 (Snellen equivalent of 20/80; P<0.001), and 60.42% (29/48) of eyes had an improvement of three lines of vision; the mean central retinal thickness significantly decreased from 333.56±171.04 µm at baseline to 187.65±54.46 µm (P<0.001), and 93.75% (45/48) achieved a dry macula. At 3 months, 6 of 32 eyes (18.75%) showed partial regression of branching vascular network, 14 of 32 (43.75%) patients showed complete resolution of polyps. The mean number of injections was 3.4±0.9 through 6 months. No conbercept-related systemic or ocular adverse effects were observed. Conclusion: Intravitreal injection of conbercept using “3+pro re nata” regimen significantly improved visual acuity and anatomical outcomes in treatment-naive patients with PCV. Keywords: conbercept, intravitreal injection, PCV, short-term efficacy, “3+PRN”